‘FEELING LIKE A NOTHING’: LEGAL AND PSYCHOLOGICAL ASPECTS OF BULLYING BY CHILDREN AND ADOLESCENTS AS UNDERSTOOD UNDER POLISH LAW - Lubelska-Sazanów, Małgorzata (Zeszyty Prawnicze, 2025)
Bullying is an extensively applied term in psychology, mostly with reference to peer violence among children and adolescents. Although Polish law penalises acts that professional publications in psychology describe as bullying, the Polish legislator has not provided a legal definition of the term “bullying” as such. The aim of this article is to present the legal mechanism used in Poland to deal with bullying, which calls for an interdisciplinary approach, not only due to the need to consider the legal and psychological literature, but also when analysing diﬀerent fields of law. Hence, most instances of bullying are subject to prosecution under the Polish Penal Code (PPC), the provisions of which may be applicable to minors in reference to the Polish Act on Juvenile Support and Rehabilitation (JSRA), but the right to damages for such actions falls within the scope of civil law and is subject to diﬀerent provisions regarding the attribution of liability and fault under Polish civil law. This empirical article confirms that parents and schools bear the responsibility for the development of children’s characters and for teaching them the right social behaviour. It also emphasises the importance of schools reacting immediately to protect and support victims of school bullying.